Chinese late‐life immigrants' loneliness and social isolation in host countries: An integrative review. Issue 9 (16th November 2021) - Zhao, Ivy Yan; Holroyd, Eleanor; Garrett, Nick; Wright‐St Clair, Valerie A.; Neville, Stephen
Abstract: Aims and objective: To synthesise current international empirical evidence on loneliness and social isolation in Chinese late‐life immigrants. Background: Loneliness causes adverse health consequences in Chinese late‐life immigrants leading to increased utilisation of often increasingly limited healthcare resources. However, little is known about how Chinese late‐life immigrants perceive and experience loneliness and social isolation in their host countries. Design: An integrative review methodology. Methods: Using a systematic search strategy, Google scholar and databases, such as Scopus, Web of Science, PubMed, CHNAHL, Medline and open access Theses were searched. No limitation was placed on publication date. Peer‐reviewed studies published from the database inception to May 6, 2021 in the English language were included. The review process is reported according to PRISMA. Results: Eight articles met the criteria and were included in this review. Two themes resulting from the data synthesis process were identified. Firstly, 'disrupted social relations after late‐life immigration' and secondly 'moving away from filial expectations'. Conclusion: Loneliness and social isolation are commonly experienced by Chinese late‐life immigrants when residing in host countries. Understanding and identification of the sources of loneliness and social isolation among late‐life immigrants are essential prompts for healthcare professionals, particularly nurses, to engage sensitively with Chinese late‐life immigrants. Nurses culturally relevant care delivery in a variety of settings may best serve recipients' social and health related needs. Relevance to clinical practice: This integrated review informs the planning of health and social services for addressing Chinese late‐life immigrants' experiences of loneliness and social isolation. Focused attention on cultural responsiveness is an important component of providing quality and safe nursing care. This review of the recent evidence on socially‐rooted health concerns affected by both immigration and ageing will help advance nursing practice in providing culturally responsive care interventions.